Analisis Faktor-Faktor yang Mempengaruhi Nilai Tukar Petani (NTP) di Indonesia Tahun 2019–2024 - Kurniawan Daud, Ian; H. Baruwadi, Mahludin; Hadi Yulia Akib , Fitri (Jurnal Paradigma Ekonomika, 2025)
This study aims to analyze factors that can affect the level of farmer welfare in 34 Indonesian provinces using the Farmer Exchange Rate (NTP) indicator from 2019 to 2024. The data used in this study are secondary data sourced from the Central Statistics Agency (BPS). The Food Crop Farmer Exchange Rate (NTPP) is the dependent variable with its independent variables being Agricultural GRDP, Rice Harvested Area, Rice Productivity, and Informal Labor in the Agricultural Sector. Data processing uses a panel data regression analysis method with a Fixed Effect Model (FEM) approach. The results show that Agricultural GRDP has a positive and significant effect on NTP, which means that increasing agricultural output encourages farmer welfare. Conversely, Rice Harvested Area has a negative and significant effect, indicating that excess supply without price control reduces farmer income. Rice Productivity and Informal Labor do not have a significant effect on NTP due to structural constraints such as unstable distribution and market prices. Simultaneously, all of these variables have a significant effect on NTP. These findings underscore the need for an integrated strategy to strengthen the agricultural sector and improve production management to boost farmer welfare.